2020
DOI: 10.1039/d0nr04140h
|View full text |Cite
|
Sign up to set email alerts
|

Machine vision-driven automatic recognition of particle size and morphology in SEM images

Abstract: A comprehensive framework to automatically perform size and morphology recognition of nanoparticles in SEM images in a high-throughput manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 25 publications
0
35
0
Order By: Relevance
“…Image recognition and mining are widely used, such as judging the growth cycle and growth situation of crops from the acquired images, judging the scale and development direction of urban construction from the acquired images. ere have been certain applications and research in various aspects in image-based recognition, tracking, and mining [6][7][8]. In terms of mechanical operation, image recognition can be used to track mechanical operations, ensure the safety of mechanical production, improve the corresponding mechanical production efficiency, realize the automation of mechanical processing, and improve the level of mechanical manufacturing in the manufacturing industry [5,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Image recognition and mining are widely used, such as judging the growth cycle and growth situation of crops from the acquired images, judging the scale and development direction of urban construction from the acquired images. ere have been certain applications and research in various aspects in image-based recognition, tracking, and mining [6][7][8]. In terms of mechanical operation, image recognition can be used to track mechanical operations, ensure the safety of mechanical production, improve the corresponding mechanical production efficiency, realize the automation of mechanical processing, and improve the level of mechanical manufacturing in the manufacturing industry [5,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Kim et al have reported an image-recognition tool that identifies the size of nanomaterials and classifies the morphology of each nanomaterial into one of the four categories: nanocubes, nanoparticles, core-shell nanoparticles, and nanorods. 57,130 The particles are located by applying a distance transform-based segmentation process on a binarized form of the image, while their size estimation tracks a similar process to that of ImageDataExtractor. 125 Kim et al identifies and extracted SEM and TEM images from the document via a different route to ImageDataExtractor, 125 employing a convolutional neural network (CNN) with transfer learning.…”
Section: Data Resource(s) Data Summary Example Usagementioning
confidence: 99%
“…[6] developed ImageDataExtractor, a pipeline to automatically mine microscopy images from literature and perform statistical analysis of particle sizes. Kim et al [7] created a tool for the size analysis of nanoparticles in SEM images, distinguishing between two broad classes of nanoparticles: core-only and core-shell nanoparticles. Hiszpanski et al [8] utilized this tool to gather insights from nanoparticle literature.…”
Section: Background and Summarymentioning
confidence: 99%
“…Annotation of ground truth bounding boxes and classes were performed using the LabelImg Past efforts on the task of label and scale detection have mostly used classical thresholdbased segmentation techniques which make use of common attributes such as the rectangular shape and white color of label and scale boxes to identify them [6], [7]. By instead using the YOLOv4 model for this task, we preclude any such prior assumptions on the size, shape, and color of scales and labels.…”
Section: Detection and Interpretation Of Labels Scales And Barsmentioning
confidence: 99%